2021
DOI: 10.1021/acs.langmuir.1c01933
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis of the Necessary and Sufficient Conditions for the Formation of Adsorption Azeotropes in Binary Gas Mixtures

Abstract: This work theoretically assessed the necessary and sufficient conditions for the formation of an adsorption azeotrope in a binary gas mixture when this mixture exhibits either intersecting or nonintersecting single gas isotherms. The thermodynamically consistent dual process Langmuir (DPL) model with equal component i saturation capacities q i,j s on site j and the general DPL model with nonequal q i,j s on site j were used for this purpose. Analytical expressions derived for both DPL models, in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…After canceling the common P terms and simplifying, eq 34 becomes a second-order expression in P , i.e., where and with its discriminant given by Again, all the possible cases of intersecting and nonintersecting single-gas isotherms resulting from eq 35 are depicted elsewhere. 39 As previously noted with the general DPL model, nonintersecting single-gas isotherms are granted only when both a g > 0 and Δ g < 0, and that it is not possible to have nonintersecting single-gas isotherms when a g < 0. These important conditions are revisited later in this work.…”
Section: Methodsmentioning
confidence: 85%
See 4 more Smart Citations
“…After canceling the common P terms and simplifying, eq 34 becomes a second-order expression in P , i.e., where and with its discriminant given by Again, all the possible cases of intersecting and nonintersecting single-gas isotherms resulting from eq 35 are depicted elsewhere. 39 As previously noted with the general DPL model, nonintersecting single-gas isotherms are granted only when both a g > 0 and Δ g < 0, and that it is not possible to have nonintersecting single-gas isotherms when a g < 0. These important conditions are revisited later in this work.…”
Section: Methodsmentioning
confidence: 85%
“…To prove the notion above, the thermodynamically consistent DPL model was used first because intersecting single-gas isotherms ensure that the corresponding binary gas mixture exhibits an adsorption azeotrope . Several sets of thermodynamically consistent DPL model parameters were found that prove adsorption azeotropes in binary gas mixtures can form at pressures above or below the intersection P of the corresponding single-gas isotherms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations